A new species of tree crickets Oecanthus (Orthoptera, Gryllidae, Oecanthinae) in tobacco plantation from Southern Brazil, with body color variation - Milach, Elisa Machado; De Martins, Luciano P.; Da Costa, Maria Kátia Matiotti; Gottschalk, Marco Silva; De Oliveira, Gabriel Lobregat; Redü, Darlan Rutz; Neutzling, Alexandre Schneid [UNESP]; Dornelles, José Eduardo Figueiredo; Vasconcellos, Lucas Azevedo; Zefa, Edison (Magnolia Press, 2015)
We provide herein a description of a new species of Oecanthus collected from the tobacco plantation in southern Brazil, municipality of São Lourenço do Sul, State of Rio Grande do Sul. Description focused metanotal gland features, phallic sclerites, and calling song. A large sampling of individuals was distributed into four groups according to body and appendages color and dotted. We also rank all kind of marks present in the scape and pedicel. We compare linear morphometric variables of the metanotal glands and tegmina, as well as calling song parameters between groups in order do define all of them as the same species. Photographs and measurements are provided.
Keywords: Bioacoustics; Ensifera; Insect; Metanotal gland; Taxonomy